Scabies and therapeutic resistance: Current knowledge and future perspectives - Gilles Absil; Eve Lebas; Florence Libon; Lara elHayderi; Bita Dezfoulian; Arjen F. Nikkels (Wiley, 2022)
Abstract Scabies is a very common ectoparasitosis and is responsible for a real scourge worldwide. The infestation leads to a highly contagious and pruritic dermatosis. Clinical diagnosis is not always easy; dermoscopy is a very useful diagnostic tool. Treatment relies on hygienic measures and specific acaricidals, either for topical application or oral administration. Ivermectin, permethrin and benzyl benzoate are the most frequently used therapies. Treatment failure is on the rise and could be attributed to noncompliance, treatment costs or to resistance to these agents. A series of novel agents are currently under investigation.